2018
DOI: 10.1037/stl0000101
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the benefits of a bachelor’s degree in psychology: Promises, challenges, and next steps.

Abstract: At the present growth rate, over 1 million undergraduate students will earn a bachelor's degree in psychology in the next 8 years. The emphasis on skills, workforce readiness, and gaps between employer expectations and graduates' skills affects psychology majors. The value of an undergraduate degree in psychology has long been questioned by the general public, and there is currently an urgent need for improved assessment of psychology majors' skills at graduation. We identify the challenges associated with mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…For instance, a recent review of undergraduate psychology programs (Norcross et al, 2016) identified that a majority of programs offer classes in over 30 different course areas (e.g., social, cognitive, abnormal), and three quarters of programs require or strongly encourage courses in abnormal, cognitive, child developmental, life span development, learning or conditioning, physiology or neuroscience, personality, sensation and perception, and social psychology. Although this breadth of training may provide some benefit to help students understand and appreciate the various subspecialties of psychology and emphasizes getting students into various psychology graduate programs (Landrum & McCarthy, 2018), it has the detrimental result of not providing a depth of training in any of these areas.…”
Section: No Clear Focus On What Is Being Trainedmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a recent review of undergraduate psychology programs (Norcross et al, 2016) identified that a majority of programs offer classes in over 30 different course areas (e.g., social, cognitive, abnormal), and three quarters of programs require or strongly encourage courses in abnormal, cognitive, child developmental, life span development, learning or conditioning, physiology or neuroscience, personality, sensation and perception, and social psychology. Although this breadth of training may provide some benefit to help students understand and appreciate the various subspecialties of psychology and emphasizes getting students into various psychology graduate programs (Landrum & McCarthy, 2018), it has the detrimental result of not providing a depth of training in any of these areas.…”
Section: No Clear Focus On What Is Being Trainedmentioning
confidence: 99%
“…Because there is a high supply of these individuals and a low demand for their expertise, companies, employers, and graduate school admission boards have no pragmatic reason to offer these individuals employment, competitive salaries, or slots in graduate school. Furthermore, it is important to note that most available resources, research, and attention are focused on undergraduates who are applying to graduate programs, even though only one quarter of students majoring in psychology go on to graduate school in psychology (Landrum & McCarthy, 2018) and only 4% go on to earn a doctorate or professional degree in psychology (Lin et al, 2017). This creates an unfortunate system where psychology departments focus on the outcomes of a select few students rather than the vast majority of students who only obtain the degree.…”
Section: Current Concerns With Undergraduate Training In Psychologymentioning
confidence: 99%
“…Try getting creative and thinking outside of the box! 37 WINTER 2019 EYE ON PSI CHI COPYRIGHT © 2019 PSI CHI P sychology students cultivate numerous skills (e.g., information seeking, computer literacy, critical thinking, problem solving, oral and written communication) through courses, research experiences, internships, volunteer work, and other activities (Landrum & McCarthy, 2018). Yet, they often struggle to market (i.e., express the value of) these skills to potential employers.…”
Section: Personal Growthmentioning
confidence: 99%
“…Try getting creative and thinking outside of the box! P sychology students cultivate numerous skills (e.g., information seeking, computer literacy, critical thinking, problem solving, oral and written communication) through courses, research experiences, internships, volunteer work, and other activities (Landrum & McCarthy, 2018). Yet, they often struggle to market (i.e., express the value of) these skills to potential employers.…”
Section: Personal Growthmentioning
confidence: 99%